The Effect of Accountability, Transparency, Rule of Law, Effectiveness and Efficiency on Local Government Performance with Supervision as A Moderating Variable in Local Government of Langkat District - Sitepu, Lia Eriska; Keulana Erwin; Idhar Yahyah (International Journal of Economics, Management and Accounting, 2025)
This study aims to analyze the influence of accountability, transparency, rule of law, effectiveness, and efficiency on local government performance with supervision as a moderating variable in the Langkat Regency Government. This study uses an associative research method with a quantitative approach based on numbers. The study population consisted of 40 Regional Work Units (SKPD) with 120 respondents determined through purposive sampling techniques, with the criteria of heads of departments/agencies, secretaries, and treasurers who have served for at least the last five years. Primary data were obtained through distributing questionnaires using a Likert scale, and data analysis was carried out with the help of SmartPLS 4.0 software. The results of the study indicate that the variables of accountability, transparency, rule of law, and effectiveness and efficiency have a positive and significant effect on local government performance. However, the results of the moderation test indicate that supervision only plays a significant role as a moderating variable in strengthening the relationship between the rule of law and local government performance. Meanwhile, supervision does not significantly moderate the relationship between accountability, transparency, and effectiveness and efficiency on local government performance. These findings are expected to be a consideration for local governments in improving the quality of governance, especially through strengthening the rule of law supported by an effective monitoring system.